Kombinasi Metode Bilqis Chastine Erma dan Sumathi Sathiya dengan Metode Stepping Stone untuk Optimasi Masalah Transportasi - Mardiansah, Rifki; Tastrawati, Ni Ketut Tari; Sari, Kartika (Department of Mathematics, Universitas Negeri Gorontalo, 2024)
Transportation problems experienced by UD. Raja Wangi in distributing Maha Dewa fragrant incense. UD. Raja Wangi incurs high transportation costs due to irregular direct distribution patterns and has not paid attention to the route to be passed. One way to solve the problem is to use transportation methods to get the optimal distribution route so that the transportation costs incurred are minimal. This study aims to solve transportation problems using the Bilqis Chastine Erma (BCE) method and the Sumathi Sathiya method with the Stepping Stone method to obtain the optimal solution. The Bilqis Chastine Erma (BCE) and the Sumathi Sathiya methods are indirect methods of solving transportation problems by obtaining an initial solution. After obtaining the initial solution, the Stepping Stone method is used to obtain the optimal solution. The results showed that the optimal solution using the Stepping Stone method based on the initial solution of the Bilqis Chastine Erma (BCE) method obtained a total transportation cost of Rp42,937.00 while the optimal solution using the Stepping Stone method based on the initial solution of the Sumathi Sathiya method obtained a total transportation cost of Rp38,727.00. In addition, the Sumathi Sathiya method gets a difference in total transportation costs of Rp11,790.00 or 23% of the total transportation costs incurred by the UD. Raja Wangi. Therefore, the Sumathi Sathiya method is the best solution for minimizing transportation costs.